Numerical simulation of hybrid additive and subtractive manufacturing and evolution behavior of stress and deformation - Shujun CHEN; Qingmian NI; Haibin LIU; Pingping CHEN; Chaoyang YAN; Ruishan XIE (Hanjie xuebao)
The final forming accuracy of additive manufacturing components depends not only on the stress accumulation and deformation during the additive manufacturing process, but also on the stress release and redistribution during milling.Therefore, a joint simulation method of hybrid additive and subtractive manufacturing was established, and the stress accumulation behavior in the process of additive manufacturing and its stress release and secondary deformation law in the subsequent material removal process were expounded. The results show that, in the process of arc additive manufacturing, there is a three-dimensional tensile stress at the interface between the part and the substrate in the first few layers and the final cooling stage. In the process of milling additive manufacturing, the residual stress is gradually released and redistributed, and the position of the maximum residual stress changes and the tensile stress decreases. At the same time, in the process of milling, the part undergoes secondary deformation, with large deformation at both ends and small deformation in the middle. The joint simulation method of hybrid additive and subtractive manufacturing proposed in this paper provides theoretical guidance for the deformation control of the final formed part.